Implementasi Model Project Based Learning Berbantuan Media Digital Dalam Meningkatkan Hasil Belajar Matematika Kelas V SD - Titin Nuraeni Titin Nuraeni; Nurkholis; Fitri Aprianti; Dedeh (Elementary Teacher Education Program, Majalengka University, 2023)
Learning in the era of digitalization needs to apply new learning models and media with interactive, innovative, and collaborative concepts in an effort to deliver materials accurately and meaningfully to learners. The aim of the research is to know the impact of the use of project-based learning models assisted by digital media on the mathematics learning outcomes of students in class V SDN Liangjulang 1. This type of research is class action research using the Kemmis & McTaggart model, carried out in 2 cycles. The subject of the study is a student of class V SDN Liangjulang 1. The data collection techniques used are observation, testing (pretest and posttest), and documentation. Data analysis techniques use quantitative analysis with inferential statistical methods. The results of this study showed that the acquisition of data on the learning outcomes of the students on the pre-test activities obtained a classical learning intensity of 44% with an average score of 65.6%, and on the post-test activities, the students obtained a classical study intensity of 84% with an average rating of 83.6%, which indicates a good category. Based on this, the use of project-based learning models with the help of digital media can improve the learning outcomes of students.